Respuesta :

[tex](5x^7 y^2) (-4x^4 y^5) = -20x^a y^b\\\\(5)(-4)x^{7+4}y^{2+5}=-20x^ay^b\\\\-20x^{11}y^7=-20x^ay^b\\\\\boxed{a=11\ and\ b=7}[/tex]

The values of a and b make the following equation true (5x^7 y^2) (-4x^4 y^5) = -20x^a y^b would be  a = 11 , b = 7.

What is a simplification of an expression?

Usually, simplification involves proceeding with the pending operations in the expression.

Like, 5 + 2 is an expression whose simplified form can be obtained by doing the pending addition, which results in 7 as its simplified form.

Simplification usually involves making the expression simple and easy to use later.

The given expression is

[tex](5x^7 y^2) (-4x^4 y^5) = -20x^a y^b\\\\\\(5) (-4x^{4+ 7} y^{5+2}) = -20x^a y^b\\\\\-20(x^{11} y^{7}) = -20x^a y^b[/tex]

here, a = 11 , b = 7.

Learn more about an expression here:

https://brainly.com/question/1249625

#SPJ2